The Appointment of Rulers from the Perspective of Bartolus of Sassoferrato - Sebastian Krafzik (Journal on European History of Law)
The document analyzes Bartolus of Sassoferrato's perspectives on the establishment of rulers, emphasizing the preference for electoral monarchy over hereditary succession. It explores Bartolus's arguments for the divine aspect of elected rulers, particularly focusing on the emperor's election, and his stance on the necessity of rulers being from the same nation or faith as their subjects. The text also discusses the broader implications of Bartolus's views on governance and the legal and constitutional backgrounds influencing his thoughts.